AFFECTIVE ASPECT ANALYSIS OF BIODIVERSITY MATERIALS USING NATURAL EXPLORE APPROACH (JAS) ASSISTED WITH EDUCATION CARD - Malinda, Annisa Lintang; Rahayuningsih, Margareta (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ Biology as one branch of science has its own characteristics compared to other natural sciences. Studying biology means attempting to know living organisms and life processes in environments that require the approach and methods to characterize and basic work in developing the concept. Learners will be more obtain the value of education when they find their own concepts about the surrounding nature through scientific process. The research objective was to determine the affective aspects of material analysis Biodiversity Approach assisted JAS Education Card. The study was conducted in June-October 2016. This study is quasy Experimental research design Nonequivalent Control Group Design. The study population throughout the class X SMA N 1 Limbangan 2016/2017 academic year was consisting of six classes. The research sample is determined by purposive sampling, ie classes and class X 5 X 6 as an experimental class and class X 2 as the control class. The data collection is done by observation. The results showed that the percentage of classical completeness the experimental class at 86.2%. Based on analysis of the experimental class, it shows affective criteria very well.